Genetic diversity based on SSR markers of 30 Aeridinae sub-tribe orchid genetic resources of Indonesian Ornamental Crop Research Institute, Cianjur, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Wegadara M, Dewanti M, Diningsih E, Rachmawati F, Sukma D, Sudarsono. 2022. Genetic diversity based on SSR markers of 30 Aeridinaesub-tribe orchid genetic resources of Indonesian Ornamental Crop Research Institute, Cianjur, Indonesia. Biodiversitas 23: 2943-2956. Advances in molecular biotechnology encourage molecular markers to identify plant diversity to become increasingly common. Using SSR markers, this study will determine the genetic diversity and phylogenetic relationships of 30 accessions from five parental genera of Aeridinaeorchids from the IOCRI genetic resource collection. Molecular characterization of 30 orchid sub-tribes Aeridinaegenetic resources of IOCRI was carried out using 17 polymorphic SSR markers. The resulting binary data was then analyzed using the GenAlEX program to determine Na, Ne, Ho, He, and the PowerMarker V3.25 program to determine the values of MAF, D, and PIC. Molecular characterization using 17 SSR primers generated 240 amplified DNA fragments across 30 accessions, with the fragment sizes ranging from 56-4818 bp. Factorial analysis (PCoA) and phylogenetic tree construction clustered the 30 Aeridinae accessions into three major clusters. Accessions belonging to the Vanda genus are clustered into three clusters (Clusters I, II, and III). The Vascostylisis in Cluster I, along with 12 Vanda accessions. Two accessions of Vanda, two Aranthera, three Arachnis, and one Aerides genera are clustered into Cluster III. This study showed that interspecific hybrids among accessions of Vanda within Cluster I and Cluster II should be possible since they are genetically closely related. Intergeneric hybrids among the accession of Vascostylis and Vanda's genera belonging to Cluster I, should also be possible. Furthermore, intergeneric hybrids among Aerides, Arachnis, Aranthera, and Vanda accessions within Cluster III should also be possible. The generated data from this study should be helpful for future Aeridinae breeding activities intended to generate new hybrid varieties.